2015
DOI: 10.1073/pnas.1420833112
|View full text |Cite
|
Sign up to set email alerts
|

Autoinhibition of MDMX by intramolecular p53 mimicry

Abstract: The p53 inhibitor MDMX is controlled by multiple stress signaling pathways. Using a proteolytic fragment release (PFR) assay, we detected an intramolecular interaction in MDMX that mechanistically mimics the interaction with p53, resulting in autoinhibition of MDMX. This mimicry is mediated by a hydrophobic peptide located in a long disordered central segment of MDMX that has sequence similarity to the p53 transactivation domain. NMR spectroscopy was used to show this hydrophobic peptide interacts with the N-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 28 publications
3
49
0
Order By: Relevance
“…4A). The K d value of (24-108) MDMX for the (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)p53 peptide is 200 nM, similar to the previously reported value of 119 nM measured by an FP-based direct binding study. 20) By contrast, (24-108)MDMX bound to (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) p53 at an affinity of 343 nM, representing a 1.7-fold decrease in p53 peptide binding affinity ascribe to the MDMX lid.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…4A). The K d value of (24-108) MDMX for the (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)p53 peptide is 200 nM, similar to the previously reported value of 119 nM measured by an FP-based direct binding study. 20) By contrast, (24-108)MDMX bound to (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) p53 at an affinity of 343 nM, representing a 1.7-fold decrease in p53 peptide binding affinity ascribe to the MDMX lid.…”
Section: Resultssupporting
confidence: 86%
“…Apparently, the binding affinities of (1-108)MDMX for three p53 peptides with different length were slightly lower than that of (24- showed that MDMX contained an auto-inhibitory sequence which is encircled near residues Trp200 and Trp201, which competed intra-molecularly for binding with p53TAD. 27,28) The binding affinity of MDMX for p53 could be increased by remove or mutation of the sequence. Our results also suggest that the flexible lid of MDMX has rare auto-inhibitory function for p53 binding.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The E2-E3 pair could play a role in substrate specificity under different cellular conditions. Another question that arises from this work is the role of intramolecular interactions that has recently been described for HDMX (45,46) and for HDM2 (40). These intramolecular interactions could add another level of regulation to the way the domains are exposed to the solvent to allow highly accurate control of the interactome of HDM2.…”
Section: Discussionmentioning
confidence: 97%